Deformation responses of the foundation pit construction of the urban metro station: A case study in Xiamen. (October 2022) - Zhao, Jinpeng; Tan, Zhongsheng; Yu, Rongsen; Li, Zonglin; Zhang, Xurui; Zhu, Pengcheng
Graphical abstract: Highlights: Deformation responses of a foundation pit in the upper-soft and lower-hard stratum are discussed. The influence of wall penetration ratios on the foundation pit is discussed. A new articulated support structure suitable for the foundation pit is proposed. The support parameters of the new articulated structure are discussed. Abstract: In the upper-soft and lower-hard stratum with weathered granite as bedrock, the deformation responses of the foundation pit during construction are quite different from that in soft soil. The deformation responses of the foundation pit were studied by on-site monitoring and numerical simulation. With the continuous excavation of the foundation pit, the construction time of the strut structures and the integrity of the support system greatly influence the deformation responses of the foundation pit. Due to the small penetration ratio of the walls, the walls have a large deflection. In addition, the ground settlement exceeds the limitation in the upper-soft and lower-hard stratum. Following the numerical simulation, the wall penetration ratios greatly influence the deformation of the foundation pit. Unlike in the soft soil stratum, the control effect of support on wall deflection in this stratum is better than that on ground settlement. The excessive force of the wall top makes the fixed constraint on the wall top very unfriendly to the bearing capacity of its adjacent concrete. Accordingly, to reduce the adverse effects caused by the fixed constraint on the wall top, a new articulated support structure was proposed and discussed by numerical simulation. The influence of the structural parameters on the deformation responses of the foundation pit was analyzed. The newly proposed support structure has a good control effect on ground settlement.